Postoperative Stereotactic Body Radiotherapy for Spinal Metastasis and Predictors of Local Control. (18th November 2021) - Blakaj, Dukagjin M; Palmer, Joshua D; Dibs, Khaled; Olausson, Alexander; Bourekas, Eric C; Boulter, Daniel; Ayan, Ahmet S; Cochran, Eric; Marras, William S; Mageswaran, Prasath; Katzir, Miki; Yildiz, Vedat O; et al.
Graphical Abstract: